Systematic review of falls in older adults with cancer. Issue 1 (January 2015) - Wildes, Tanya M.; Dua, Priya; Fowler, Susan A.; Miller, J. Philip; Carpenter, Christopher R.; Avidan, Michael S.; Stark, Susan
Abstract Objectives Older adults frequently experience falls, at great cost to themselves and society. Older adults with cancer may be at greater risk for falls and have unique risk factors. Materials and methods We undertook a systematic review of the available medical literature to examine the current evidence regarding factors associated with falls in older adults with cancer. PubMed, Embase, CINAHL, CENTRAL, DARE, Cochrane Database of Systematic Reviews and clinical trials.gov were searched using standardized terms for concepts of oncology/cancer, people 60 and older, screening, falls and diagnosis. Eligible studies included cohort or case-control studies or clinical trials in which all patients, or a subgroup of patients, had a diagnosis of cancer and in which falls were either the primary or secondary outcome. Results We identified 31 studies that met our inclusion criteria. Several studies suggest that falls are more common in older adults with a diagnosis of cancer than those without. Among the 11 studies that explored factors associated with outpatient falls, some risk factors for falls established in the general population were also associated with falls in older adults with cancer, including dependence in activities of daily living and prior falls. Other factors associated with falls in a general population, such as age, polypharmacy and opioid use, were not predictive of falls among oncology populations. Falls among older adults with cancer in the inpatient setting were associated with established risk factors for falls in people without cancer, but also with factors unique to an oncology population, such as brain metastases. Conclusions Falls in older adults with cancer are more common than in the general population, and are associated with risk factors unique to people with cancer. Further study is needed to establish methods of screening older adults with cancer for fall risk and ultimately implement interventions to reduce their risk of falls. Identifying which older adults with cancer are at greater risk for falls is a requisite step to ultimately intervene and prevent falls in this vulnerable population.